The implementation of evaluation in Science learning based on Problem Based Learning (PBL) for 3rd graders during Covid-19 pandemic outbreak - Ofta Dwi Purwantini; Wahyu Lestari (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2021)
This study aimed to analyze the implementation of evaluation in Science learning at 3rd grade in SD IT Asshodiqiyah Semarang. This study used the qualitative method and collected data through observation, interview and documentation. The data source of the study was the teacher, parents, and students. During the Covid-19 pandemic outbreak, SD IT Asshodiqiyah conducted learning through the WhatsApp platform. The result of the study obtained some findings as follows: (1) PBL-based learning evaluation was appropriate to implement in Science learning, (2) PBL-based evaluation was conducted according to the objectives of learning by following simple yet challenging learning stages for students to involve in active participation, (3) evaluation in Science learning were in portfolio-based model, practice-based model, and cognitive-based model by using WhatsApp platform and Google Form feature. Nevertheless, the authors found some obstacles in the implementation, such as the lack of parents' and student enthusiasm, the lack of parent understanding on how to implement the evaluation model, and the lack of cooperation between teacher and parents. The solution for the problem was that teachers and parents should have good communication and mutual agreement regarding the evaluation process.